A case report of cognitive behavioral therapy for social anxiety - Xu, Feifei; Zhang, Hang (Frontiers in Psychology, 2025)
ObjectiveTo develop a case conceptualization consultation plan for social anxiety cognitive behavioral therapy (CBT).MethodsFirstly, according to the process and requirements of case conceptualization, the content of the case is presented to the customer in the form of conceptual model diagram. Subsequently, according to the specific problems raised in each part, targeted interventions were implemented by means of exposure, cognitive reconstruction, inhibition of safe behaviors, etc., and the intervention was divided into eight stages, all the patients were assessed before and after the consultation.ResultsBefore the intervention, the patient SCL-90 scale, total score 190, somatization: 2.1, interpersonal sensitivity: 2.2, depression: 2.1, and anxiety: 2.7. Fear Factor Score: 2.4, other factor score <2, positive item 45, significant anxiety symptoms; SAS: score 65; social avoidance and distress scale-SAD-SAD total score of 20; It showed that the patients had significant social anxiety in social interaction. After the intervention, Scl-90: Total score of 140, score of <2 for each factor, number of positive items of 30, and all indicators returned to normal: SAS: standard score of 49: SDS: Standard score of 38, no depressive mood. The total score of SAD was 14, with a score of 5 for avoidance and 9 for anxiety, indicating improvement in social anxiety.ConclusionThe case conceptualization approach in social anxiety CBT consultations facilitates patients with social anxiety issues in understanding their problems, demonstrating practical application value in psychological counseling.